BIOLOGIC THERAPY AND QUALITY OF LIFE IN NSAID-EXACERBATED RESPIRATORY DISEASE: A SYSTEMATIC REVIEW OF SNOT-22 PATIENT-REPORTED OUTCOMES - Laske , Alicja; Majda, Antoni; Sitko , Natalia; Makowska , Paulina; Gontarczyk , Joanna; Sowa, Martyna; Pająk, Julia; Kucharski , Kacper; Kamosińska , Anna; Kowal, Adam; Sokołowska, Julia; Dawidowicz, Marcel (International Journal of Innovative Technologies in Social Science, 2026)
Background: Nonsteroidal anti-inflammatory drug-exacerbated respiratory disease (N-ERD) is a severe, refractory phenotype of chronic rhinosinusitis with nasal polyps (CRSwNP) and asthma. Traditional treatments, including repeated endoscopic sinus surgeries and aspirin therapy after desensitization (ATAD), are frequently limited by high recurrence and discontinuation rates, leaving a critical unmet need for durable symptom control.Objective: To systematically evaluate the impact of targeted biologic therapies on patient-reported quality of life in the N-ERD population, utilizing the 22-item Sino-Nasal Outcome Test (SNOT-22).Methods: A systematic literature search of PubMed and Scopus was conducted between January and March 2026. Eligibility criteria strictly isolated studies reporting longitudinal, continuous SNOT-22 data for adult N-ERD cohorts treated with monoclonal antibodies.Results: Eight studies met the inclusion criteria. Pre-treatment SNOT-22 scores confirmed severe baseline disability across all cohorts.Treatment with the anti-IL-4Rα agent dupilumab rapidly transformed patient outcomes, yielding clinically meaningful SNOT-22 score reductions ranging from 27 to 48 points, which were sustained for up to two years.Dupilumab demonstrated robust efficacy in restoring olfactory function and improving asthma control. While anti-IL-5 therapies (mepolizumab) provided clinical benefit, comparative data indicated they were less consistently effective at normalizing olfaction and achieving comprehensive symptom resolution than dupilumab.Conclusion: Targeted biologic therapies, particularly dupilumab, deliver significant improvements in quality of life for patients with N-ERD. They represent a highly effective, non-surgical step-up therapy capable of halting the surgical cycle and achieving profound symptom relief in treatment-refractory patients.